Karakteristik Keuangan dan Non Keuangan pada Kualitas Sustainability Disclosure Perusahaan Manufaktur di Indonesia - Dewi, Luh Gede Krisna; Ariyanto, Dodik; Amara, Anisa Virdawati (E-Jurnal Akuntansi; Vol 34 No 1 (2024)DO - 10.24843/EJA.2024.v34.i01.p01, 2024)
Company transparency related to commitment to achieving SDGs as well as impacts on the environment and social is conveyed through sustainability disclosures. This research aims to empirically analyze the influence of financial characteristics (profitability and leverage) and non-financial characteristics (gender, age, educational background, tenure of the President Director and nationality) on the quality of sustainability disclosure of manufacturing companies in Indonesia. The research uses panel data regression analysis techniques with the Eviews 12 analysis tool and uses a population of manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period. Based on the purposive sampling technique, a sample of 75 observations was obtained. The research results found that leveraged financial characteristics have a positive effect on the quality of manufacturing companies' sustainability disclosures. Meanwhile, non-financial characteristics in the form of individual characteristics of the President Director have no effect on the quality of manufacturing companies' sustainability disclosures. The research findings provide an insight into the level of sustainability disclosure in terms of organizational characteristics and individual decision makers. Keywords: Profitability; Leverage; Gender; Age; Sustainability Disclosure.